Beauty in Hegel's Anthropology and philosophy of art - Peters, Julia (Idealistic studies, 2013)
According to a widespread view, Hegel holds that beauty cannot be found in the creatures and objects of the natural world, but is strictly limited to works of art. I argue in this paper that Hegel’s restriction of beauty to works of art is not as straightforward as it is often taken to be, by showing that the phenomenon of beauty has anthropological roots in Hegel. Juxtaposing the Lectures on Aesthetics with sections from Hegel’s Anthropology in the Encyclopedia of Philosophical Sciences, I demonstrate that the living human individual has considerable aesthetic potential in Hegel’s view. According to the interpretation developed in the paper, Hegel holds that artistic beauty—at least in its classical form—is inspired by the beauty of the living human individual. This interpretation makes emerge a strong, ambitious conception of artistic beauty according to which beautiful art not only stands in continuity with human nature, but also makes normative claims pertaining to the living human individual.